SOCIALLY RESPONSIBLE INVESTMENT IN ASIA - Kłobukowska, Justyna (Copernican Journal of Finance & Accounting, 2017)
The main goal of the article is to characterize and analyze the socially responsible investment in Asia. Choice of the subject was dictated the lack in knowledge about Asian SRI market. There are many differences in a scope and actual development levels of the SRI market between Asian countries. The paper is divided into three major parts. The first part is related to characteristic of socially responsible investment. The second part of the article is dedicated to institutional view on SRI market in Asia. In the third part the attention is paid to statistical data concerning socially responsible investment market in Asia as well as main directions of SRI development in this region. The literature of the subject and data published by the organizations which are involved in promotion SRI were analyzed for the purpose of this article.